Development of Chemical Sensor Based on Fatty Hydroxamic Acid for The Determination of Vanadium (V) and Iron (Iii) Ions - Isha, Azizul (2005)
Chemical sensor based on the use of uv-visible spectrophotometer and optical fibre reflectance spectrometer (OFRS) for the determination of Fe(II1) and V(V) ions have been developed in this study. Fatty hydroxamic acid (FHA) was used as a reagent for both metals and shows good properties after characterization using manual batch method. FHA immobilized on poly(viny1 chloride) (PVC) and poly(methy1 methacrylate) (PMMA) as sensing membranes were successfully applied for determination of V(V). However, both immobilization processes were not showing any measurable signal in determination of Fe(II1). PMMA membrane immobilized FHA was characterized using uv-visible spectrophotometer. The sensing membrane changed fiom colorless to dark purple in the presence of V(V) with response time of five minutes. The relative standard deviation (RSD) of the reproducibility were found to be 9.29% and 7.09% for V(V) at concentration of 50 ppm and 200 ppm, respectively.Interference fiom foreign ions were studied at 1:l mole ratio of V(V) to interfering ion. The interference faced by Fe(II1) was the greatest when it was compared with other cations, whereas phosphate ion gave the highest anion interferences. The limit of detection of the PMMA membrane immobilized FHA was calculated to be 8.4 ppm. PVC membrane immobilized FHA was characterized using optical fibre reflectance spectrometer. The sensing membrane changed its color from colorless to purple in the presence of V(V) and with response time of five minutes. The RSD of the reproducibility were found to be 3.91% and 3.85% for V(V) at concentration of 1 ppm and 20 ppm, respectively. Interference from foreign ions were studied at 1 : 1 mole ratio of V(V) to interfering ion. Fe(II1) was found to interfere most compared to other cations, whereas citrate gave the highest anion interferences. The limit of detection of the PVC membrane immobilized FHA was calculated to be 0.1 ppm. The results obtained from both instruments which have been developed in this study were compared with the well established method of inductively coupled plasma-atomic emission spectroscopy (ICP-AES). The comparison results show an excellent agreement between the developed method and ICP-AES method. This indicates that the results obtained fiom both methods are comparable.